Legal Protection Against Occupational Safety and Health (K3) at PT. Geo Dipa Energi Wonosobo Based on the Law of the Republic of Indonesia Number 1 of 1970 on Occupational Safety - Allan Ardi Riyayan (UM Purwokerto Press, 2023)
Legal protection is to provide protection for human rights (HAM) that are harmed by others and the protection is given to the community in order to enjoy all the rights granted by law, legal protection of occupational safety and health is regulated in Law No. 1 of 1970 concerning Occupational Safety. The normative-empirical research method is legal research based on legal research that not only examines the system of norms in legislation, the method of analysis used in this research is to use qualitative data. The protection provided to workers of PT Geo Dipa Energi Wonosobo is in accordance with applicable laws and regulations such as matters related to employment relationships, long contract agreements are returned to the agreement mechanism for the parties, namely the worker and the employer through an agreement called a work agreement, collective labor agreement or company regulation.